Findbuch des Bestandes Abt. 65.1-65.3 Deutsche Kanzlei zu Kopenhagen bis 1730 | Deutsche Kanzlei zu Kopenhagen ab 1730 | Deutsche Kanzlei zu Kopenhagen für das Herzogtum Lauenburg - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2019)
The German Chancery - since 1806 the Schleswig-Holstein Chancery, from 1816 on the Schleswig-Holstein-Lauenburg Chancery - developed from the early 16th century, and acquired fixed institutional forms in the 17th century. Its territorial jurisdiction initially extended to the royal portions, from 1773 to the entire Duchies of Schleswig and Holstein, and from 1816 additionally to the Duchy of Lauenburg. From 1667 to 1773, the counties of Oldenburg and Delmenhorst were also part of the Chancellery's portfolio. As the highest and most important royal authority for the duchies with its seat in Copenhagen, the Chancellery had a comprehensive area of competence. It was responsible for the entire internal administration of the country, unless individual tasks were assigned to special administrative authorities, such as the Chamber of Pensions. In addition, the Chancellery was also responsible for the foreign affairs of the Danish kingdom until the Department of Foreign Affairs was established for this purpose in 1770. The records of the German Chancellery are of outstanding importance for research on both Schleswig-Holstein and Danish history. This special value of the Chancery Archives is the reason why they are divided between the Reich Archives in Copenhagen and the Schleswig-Holstein State Archives: Copenhagen holds the bulk of the older records before 1730, while the Landesarchiv holds the bulk of the records from 1730 onwards.The written records of the German Chancellery in the Landesarchiv presented in this finding aid are among the most important holdings from the period from the 16th to the mid-19th century that the Landesarchiv has available for research.